Sie sind auf Seite 1von 6

LIST OF IMPORTANT MATH FORMULAS AND RESULTS

Algebra:
? Laws of Indices:
(i) am an = am + n
(ii) am/an
(iii) (am)n = amn
(iv) a0 = 1 (a ? 0).
(v) a- n = 1/an
(vi) nvam = am/n
(vii) (ab)m = am bn.
(viii) (a/b) m = am/bn
(ix) If am = bm (m ? 0), then a = b.
(x) If am = an then m = n.

? Surds:
(i) The surd conjugate of va + vb (or a + vb) is va - vb (or a - vb) and convers
ely.
(ii) If a is rational, vb is a surd and a + vb (or, a - vb) = 0 then a = 0 and b
= 0.
(iii) If a and x are rational, vb and vy are surds and a + vb = x + vy then a =
x and b = y.

? Complex Numbers:
(i) The symbol z = (x, y) = x + iy where x, y are real and i = v-1, is called a
complex (or, imaginary) quantity;x is called the real part and y, the imaginary
part of the complex number z = x + iy.
(ii) If z = x + iy then z = x - iy and conversely; here, z is the complex conjug
ate of z.
(iii) If z = x+ iy then
(a) mod. z (or, | z | or, | x + iy | ) = + v(x2 + y2) and
(b) amp. z (or, arg. z) = ? = tan-1 y/x (-p < ? = p).
(iv) The modulus - amplitude form of a complex quantity z is
z = r (cos? + i sin?); here, r = | z | and ? = arg. z (-p < ? <= p).

(v) | z | = | -z | = z z = v (x2 + y2).


(vi) If x + iy= 0 then x = 0 and y = 0(x,y are real).
(vii) If x + iy = p + iq then x = p and y = q(x, y, p and q all are real).
(viii) i = v-1, i2 = -1, i3 = -i, and i4 = 1.
(ix) | z1 + z2| = | z1 | + | z2 |.
(x) | z1 z2 | = | z1 | | z2 |.
(xi) | z1/z2| = | z1 |/| z2 |.
(xii) (a) arg. (z1 z2) = arg. z1 + arg. z2 + m
(b) arg. (z1/z2) = arg. z1 - arg. z2 + m where m = 0 or, 2p or, (- 2p).
(xiii) If ? be the imaginary cube root of unity then ? = (- 1 + v3i) or, ? = (-1
- v3i)
(xiv) ?3 = 1 and 1 + ? + ?2 = 0

? Variation:
(i) If x varies directly as y, we write x ? y or, x = ky where k is a constant o
f variation.
(ii) If x varies inversely as y, we write x ? 1/y or, x = m (1/y) where m is a c
onstant of variation.
(iii) If x ? y when z is constant and x ? z when y is constant then x ? yz when
both y and z vary.

? Arithmetical Progression (A.P.):


(i) The general form of an A. P. is a, a + d, a + 2d, a+3d,.....
where a is the first term and d, the common difference of the A.P.
(ii) The nth term of the above A.P. is tn = a + (n - 1)d.
(iii) The sum of first n terns of the above A.P. is s = n/2 (a + l) = (No. of te
rms/2)[1st term + last term] or, S = n/2 [2a + (n - 1) d]
(iv) The arithmetic mean between two given numbers a and b is (a + b)/2.
(v) 1 + 2 + 3 + ...... + n = [n(n + 1)]/2.
(vi) 12 + 22 + 32 +

. + n2 = [n(n+ 1)(2n+ 1)]/6.

(vii) 13 + 23 + 33 + . . . . + n3 = [{n(n + 1)}/2 ]2.

? Geometrical Progression (G.P.) :

(i) The general form of a G.P. is a, ar, ar2, ar3, . . . . . where a is the firs
t term and r, the common ratio of the G.P.
(ii) The n th term of the above G.P. is tn = a.rn - 1 .
(iii) The sum of first n terms of the above G.P. is S = a [(1 - rn)/(1
-1 < r < 1
or, S = a [(rn

1)/(r

r)] when

1) ]when r > 1 or r < -1.

(iv) The geometric mean of two positive numbers a and b is v(ab) or, -v(ab).
(v) a + ar + ar2 +

. 8 = a/(1

r) where (-1 < r < 1).

? Theory of Quadratic Equation :


ax2 + bx + c = 0 ... (1)
(i) Roots of the equation (1) are x = {-b v(b2

4ac)}/2a.

(ii) If a and be the roots of the equation (1) then,


sum of its roots = a + = - b/a = - (coefficient of x)/(coefficient of x2 );
and product of its roots = a = c/a = (Constant term /(Coefficient of x2).
(iii) The quadratic equation whose roots are a and is
x2 - (a + )x + a = 0
i.e. , x2 - (sum of the roots) x + product of the roots = 0.
(iv) The expression (b2 - 4ac) is called the discriminant of equation (1).
(v) If a, b, c are real and rational then the roots of equation (1) are
(a) real and distinct when b2 - 4ac > 0;
(b) real and equal when b2 - 4ac = 0;
(c) imaginary when b2 - 4ac < 0;
(d) rational when b2- 4ac is a perfect square and
(e) irrational when b2 - 4ac is not a perfect square.
(vi) If a + i be one root of equation (1) then its other root will be conjugate c
omplex quantity a - i and conversely (a, b, c are real).
(vii) If a + v be one root of equation (1) then its other root will be conjugate
irrational quantity a - v (a, b, c are rational).

? Permutation:
(i) ?n (or, n!) = n (n

1) (n

2) 321.

(ii) 0! = 1.
(iii) Number of permutations of n different things taken r ( = n) at a time nPr
= n!/(n - 1)! = n (n
1)(n - 2) (n - r + 1).
(iv) Number of permutations of n different things taken all at a time = nPn = n!
.
(v) Number of permutations of n things taken all at a time in which p things are
alike of a first kind, q things are alike of a second kind, r things are alike
of a third kind and the rest are all different, is n!/(p!q!r!)
(vi) Number of permutations of n different things taken r at a time when each th
ing may be repeated upto r times in any permutation, is nr .

? Combination:
(i) Number of combinations of n different things taken r at a time = nCr = n!/(r
!(n r)!).
(ii) nPr = r! nCr.
(iii) nC0 = nCn = 1.
(iv) nCr = nCn - r.
(v) nCr + nCn - 1 = n + 1Cr
(vi) If p ? q and nCp = nCp then p + q = n.
(vii) nCr/nCr - 1= (n - r + 1)/r.
(viii) The total number of combinations of n different things taken any number a
t a time = nC1 + nC2 + nC3 +
. + nCn = 2n
1.
(ix) The total number of combinations of (p + q + r + . . . .) things of which p
things are alike of a first kind, q things are alike of a second kind r things
are alike of a third kind and so on, taken any number at a time is [(p + 1) (q +
1) (r + 1) . . . . ] - 1.

? Binomial Theorem:
(i) Statement of Binomial Theorem : If n is a positive integer then
(a + x)n = an + nC1 an - 1 x + nC2 an - 2 x2 +

.. + nCr an - r xr +

.. + xn

.. (1)

(ii) If n is not a positive integer then


(1 + x)n = 1 + nx + [n(n - 1)/2!] x2 + [n(n - 1)(n - 2)/3!] x3 +
+1)}/r!] xr+
. 8 (-1 < x < 1)
.(2)

+ [{n(n-1)(n-2)

..(n-

(iii) The general term of the expansion (1) is (r+ 1)th term
= tr + 1 = nCr an - r xr
(iv) The general term of the expansion (2) is (r + 1) th term
= tr + 1 = [{n(n - 1)(n - 2)....(n - r + l)}/r!] xr.
(v) There is one middle term is the expansion ( 1 ) when n is even and it is (n/
2 + 1)th term ; the expansion ( I ) will have two middle terms when n is odd and
they are the {(n - 1)/2 + 1} th and {(n - 1)/2 + 1} th terms.
(vi) (1 - x)-1 = 1 + x + x2 + x3 +
(vii) (1 + x)-1 = I - x + x2 - x3 +

.8.
8.

(viii) (1 - x)-2 = 1 + 2x + 3x2 + 4x3 + . . . . 8 .


(ix) (1 + x)-2 = 1 - 2x + 3x2 - 4x3 + . . . . 8 .

? Logarithm:
(i) If ax = M then loga M = x and conversely.
(ii) loga 1 = 0.
(iii) loga a = 1.
(iv) a logam = M.
(v) loga MN = loga M + loga N.
(vi) loga (M/N) = loga M - loga N.
(vii) loga Mn = n loga M.
(viii) loga M = logb M x loga b.
(ix) logb a x 1oga b = 1.
(x) logb a = 1/logb a.
(xi) logb M = logb M/loga b.

? Exponential Series:
(i) For all x, ex = 1 + x/1! + x2/2! + x3/3! +
(ii) e = 1 + 1/1! + 1/2! + 1/3! +

+ xr/r! +

.. 8.

.. 8.

(iii) 2 < e < 3; e = 2.718282 (correct to six decimal places).


(iv) ax = 1 + (loge a) x + [(loge a)2/2!] x2 + [(loge a)3/3!] x3 +

.. 8.

? Logarithmic Series:
(i) loge (1 + x) = x - x2/2 + x3/3 (ii) loge (1 - x) = - x - x2/ 2 - x3/3 -

8 (-1 < x = 1).


.. 8 (- 1 = x < 1).

(iii) loge [(1 + x)/(1 - x)] = x + x3/3 + x5/5 +


(iv) loge 2 = 1 - 1/2 + 1/3 - 1/4 +

8 (-1 < x < 1).

8.

(v) log10 m = loge m where = 1/loge 10 = 0.4342945 and m is a positive number.